2009
DOI: 10.1017/s1368980009991327
|View full text |Cite
|
Sign up to set email alerts
|

Are fish eaters healthier and do they consume less health-care resources?

Abstract: Objective: Regular dietary intake of fish is associated with reduced risk of developing cardiovascular and other chronic diseases, and may improve general well-being. If fish eaters are healthier, they may use fewer health-care resources. The present study aimed to describe the reported intake of fish and fish products in a Danish general population, and to investigate whether fish consumption is associated with generic measures of self-reported health and consumption of health-care resources. Design: Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The nutritional benefit of a diet rich in seafood and oily fish in particular extends beyond n-3 LC-PUFAs content. Fish, as a whole food, is an excellent source of lean protein and other vitamins and minerals including vitamins A and D, B group vitamins, iron, zinc, selenium and iodine (Hostenkamp & Sorensen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional benefit of a diet rich in seafood and oily fish in particular extends beyond n-3 LC-PUFAs content. Fish, as a whole food, is an excellent source of lean protein and other vitamins and minerals including vitamins A and D, B group vitamins, iron, zinc, selenium and iodine (Hostenkamp & Sorensen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there wasn't a strong directional association between sex and seafood consumption observed. Seafood consumption was higher in men than in women in thirteen papers (13,16,18,22,29,31,(52)(53)(54)(59)(60)(61)(62) as Accepted manuscript opposed to eleven papers (13,24,32,34,37,40,51,(54)(55)(56)63) finding that women were more likely to consume seafood. Two of these studies found that men are more likely to consume fried fish (13,54) , and according to three studies women were more likely to consume non-fried fish (13,54,63) .…”
Section: Sexmentioning
confidence: 96%
“…Thirty-six papers found a significant association between education and seafood consumption. Most of these studies highlighted a positive association between education level and seafood consumption (14)(15)(16)18,23,(26)(27)(28)(29)(30)(36)(37)(38)(39)41,42,45,46,(51)(52)(53)(54)(55)(57)(58)(59)63,64,71,73,(80)(81)(82)(83)(84) . An association between higher education and non-fried fish consumption, as well as an association between lower education level and fried fish consumption, was reported in two papers (54,57) .…”
Section: Characteristics Of Seafood Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish is an excellent source of lean protein, omega-3 polyunsaturated fatty acids and micronutrients, including vitamins A and D, B group vitamins, iron, zinc, selenium and iodine (Hostenkamp and Sorensen, 2009). Regular consumption of fish and seafood has been linked with health benefits relating to coronary heart disease, heart failure, sudden death, some cancers, rheumatoid arthritis, neurological development, dementia, Alzheimer's disease and depression (Hibbeln, 1998;Morris et al, 2003;Hibbeln et al, 2007;Newton and McManus, 2011;McEvoy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%